Pengaruh penerapan LKS berorientasi pembelajaran terpadu tipe jaring laba-laba terhadap kompetensi IPA siswa kelas VII SMPN 1 Bukittinggi - Eko Muda Setiawan; Hidayati Hidayati; Letmi Dwiridal (PILLAR OF PHYSICS EDUCATION, 2019)
Competence of students in Science subjects in grades VII SMP Negeri 1 Bukittinggi has not reached Minimum Criteria of Mastery Learning (KKM). This may be due to several factors, such as: models and strategies used in the activities of teacher learning less diverse; the learning activities of students just listen and take note of what is delivered by teachers; the teacher in the learning process often uses a Lecture Method; as well as the Worksheets Students (LKS) available yet to describe the interrelatedness between physics, biology, and chemistry. Therefore, research is conducted to provide solutions by applying Student Worksheets oriented Webbed toward the competency of the IPA student grade VII SMP Negeri 1 Bukittinggi.To achieve the goal  of the research, performed research experiment with pseudo Randomized Control Group Only Design. This research population is the student grade VII  SMP Negeri 1 Bukittinggi school year 2017/2018 and take sampling by the Technique of Purposive Sampling. Research instrument used in the form of a written test for knowledge and competence performance using scoring rubrics for competency skills. The data obtained were analyzed using analysis of similarity of two averages for competence of knowledge and competency skills.The results showed the average value of the competency of the IPA at both the class samples and 56.94 to 70.56  "competence knowledge ", and 85.98 and 82.92 for competency skills. The test of t’, retrieved t’hitung>t’tabel. So, the working hypothesis accepted for competence of knowledge, whereas for competency skills of test t, retrieved t’hitung>t’tabel. So, the working hypothesis accepted. Conclusion of the research was the hypothesis that States that there are influences which means application of Worksheets Students integrated learning-oriented Webbed toward the competency of the IPA student grade VII SMP Negeri 1 Bukittinggi.